O salto do cinema brasileiro contemporâneo no céu do sertão: uma análise dos filmes O Céu de Suely e Viajo porque preciso, volto porque te amo - Santos, Márcia Vanessa Malcher dos (2014)
The purpose of this research is to think about the representation of the sertão in contemporary Brazilian cinema , from the analysis of two recent films, O Céu de Suely (Karim Aïnouz, 2006) and Viajo porque preciso, volto porque te amo (Karim Aïnouz; Marcelo Gomes, 2010). To this end , we seek to understand the social implications of the sertão‟s denser moments in the national cinema, establishing a fundamental and necessary link between the present and the past. Furthermore, we investigated the relationship between cinema, state and market in the country in order to define the basis of current production and situate the place occupied by cinema from the Northeast in Cultural Industry, which comprises the filmmakers Karim Aïnouz and Marcelo Gomes . Finally, we turn to the chronotope concept of Mikhail Bakhtin, as analytical axis , to think about the dislocate‟s poetics, the remarkable presence of the road and nomadic individuals in the films analyzed. The aim is to map, dialectically, the forms of time and space in the narratives of O Céu de Suely and Viajo porque preciso, volto porque te amo and in the postmodern sociality of which they are part.